Developing teacher identity among music performance students - Bennett, Dawn (Monash University, 2009)
The mythologised image of the musician as performer often contradicts the reality. This article reports initial results from a study that used learner-generated drawings and journal reflections with music performance majors as a means to examine emerging perceptions of music teaching. Whilst initial drawings illustrated traditional images of the teacher as knowledge giver, these gave way to more fluid and student-centred images in which students appeared to identify with teaching in new ways. The combination of textual and non-textual data provided insights that would not otherwise have been evident, and the broad consideration of 'possible selves' became a useful tool in the explorations of identity and career.